Evaluation sozialpolitischer Reformen - Patrick A. Puhani; Katja Sonderhof (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This paper illustrates the evaluation of changes in social policy regulations with respect to two reforms that strengthened the rights of either employers or employees. Causal effects of the reform are based on control group designs (difference-in-differences estimates). The results show that interventions of the state in the labor market also have negative effects - besides the desired supportive/distributional effects for sick people in one case and for parents in the other. The regulation that the employer has to pay an absent sick worker 100 instead of 80 percent of the wage increases the average days of absence from work from about 6 to 8 days (estimates vary by specification, some estimates even exhibit higher effects), without significantly negatively affecting subjective health indicators. The regulation that demands employers to guarantee comparable employment to a parent even after 3 years of absence reduces employer-arranged training for young women.
Keywords: I18; J16; J24; J83; 330; Sozialpolitik - Reform; Reformpolitik - Auswirkungen; Beschäftigungseffekte; Erziehungsurlaub; Lohnfortzahlung; Krankenstand; Arbeitnehmer; Tarifvertrag; Fehlzeiten; junge Erwachsene; Frauen; betriebliche Weiterbildung; Weiterbildungsbeteiligung; Bildungschancen